True to you - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Montana heat., 2018)
Undercover DEA Special Agent Dawson King spent five months in a Montana prison establishing a fake identity to take down a ruthless drug dealer and put him behind bars. Except there's a wild card...the killer's beloved daughter. Cara Potter may appear to be on the right side of the law, but King has learned the hard way to trust no one--even someone as tantalizing as the coffer shop owner. She's irresistible...but is she also dangerous?--from Publishers description.